Cultural aspects of organizational agility affecting digital innovation - Dulce Goncalves; Magnus Bergquist; Richard Bunk; Sverker Alänge (Journal of Entrepreneurship, Management and Innovation)
The purpose of this study is to understand how the cultural aspects of organizational agility affect digital innovation capability. In the context of increasing demand for fast-paced digital innovation, organizational agility becomes strategically crucial for large incumbent companies to increase their competitiveness. The literature on organizational agility shows that incumbents, with their vast access to resources, still can have limited ability to innovate and respond to change. This is in sharp contrast to startups, who sometimes are impressively innovative despite their very limited resources. Sometimes the incumbents are even outcompeted and disrupted by startups because of their ability to embrace change, and rapidly seize new business opportunities. However, we know little about why some incumbents are not able to use their resources efficiently for digital innovation and why some smaller startups can transcend these resource limitations. In this context, we find that cultural aspects are especially crucial as enablers for organizational agility in digital innovation. We designed a comparative study to investigate the differences in the influence of culture on organizational agility; and how it hinders or enables digital innovation, at both incumbent firms and startups in the automotive industry. We applied a qualitative research approach and selected semi-structured interviews as our main research method. The Competing Values Framework was used as a tool to categorize different cultures that affect organizational agility, but also to identify how and when tensions between values supported or hampered the organizations’ ability to innovate. Our findings show that, while a blend of Hierarchy and Market cultures inhibited the innovation capability, Clan and Adhocracy cultures promoted innovation. In our sample, the incumbents predominantly adhered to the first two cultures, while the startups typically belonged to the second group. The most successful startups were even able to create a combination of Clan and Adhocracy cultures — a concept we here term ‘Agile culture.’ This culture allowed them to reach a beneficial state of digital innovation growth. When it comes to the implications for research and practice, we found the need to analyze the role of culture for organizational agility; and how to utilize culture as an asset to enable digital innovation growth. One contribution is the identification of ‘Agile culture’ that is an amalgamation of Clan and Adhocracy culture. The value agile culture creates when applied, enables organizational agility, which can enhance digital innovation capability.